Design of wideband CMOS low-noise amplifiers for ultra-wideband receivers - Lu, Yang (2011)
The ultra-wideband (UWB) wireless transmission system is drawing tremendous attention from both the industry and the academia because of its unique potential to supply the gap for short-range high-speed wireless data communication. The WiMedia Alliance’s Multi-Band Orthogonal Frequency Division Multiplexing (MB-OFDM) proposal finished its standardization with the European Computer Manufacturers Association International (Ecma International) and has virtually become the industry standard for the UWB wireless transmission systems. The ultra-wideband low-noise amplifier (LNA), which is the first building block in an integrated UWB receiver, is of significant importance to the performance of the whole receiver chain. By reviewing the worldwide UWB regulations and the WiMedia Alliance’s MB-OFDM UWB standard, it is well understood that the ultra wide bandwidth required for the UWB low-noise amplifier calls for a different set of target specifications and trade-offs comparing with conventional narrow-band LNAs. Thus, novel circuit architectures need to be investigated and established for UWB LNAs to achieve these specifications.